Iodine‐modified Pt nanoparticles accelerate the hydrogenative ring‐opening of furfurals to linear alcohols. Issue 5 (22nd December 2022) - Zhang, Likang; Li, Xiang; Wang, Jun; Zeng, Zheling; Yang, Weiran; Deng, Shuguang; Deng, Qiang
Abstract: The hydrogenative ring‐opening of furfurals (furfural and 5‐methylfurfural) to linear diols (1, 4‐pentanediol and 2, 5‐hexanediol) is of great significance for bioderived fine chemical synthesis. Unfortunately, the catalytic activity and selectivity are unsatisfactory because of the interference of various side reactions, such as overhydrogenation to tetrahydrofurans. Herein, the preparation of an iodine (I) modified Pt‐based catalyst with abundant Pt‐I pairs is reported for the first time and shows high catalytic efficiency for linear diol synthesis with a yield of 80%–90% via the hydrogenative ring‐opening route, whereas bare Pt counterpart only shows tetrahydrofuran synthesis via the overhydrogenation route. The catalytic reaction mechanism shows the in‐situ hydrogen spillover‐promoted H − ‐Pt‐I‐H + pairs not only supply hydrogenation sites for the C=O hydrogenation step but also provide Brønsted acidic sites for the ring‐opening step. This work presents a feasible and convenient strategy for bifunctional catalysis with powerful linear diol synthesis over iodine‐modified noble metals.